Combination of a structured aerobic and resistance exercise improves glycaemic control in pregnant women diagnosed with gestational diabetes mellitus. A randomised controlled trial. Issue 4 (August 2018) - Sklempe Kokic, Iva; Ivanisevic, Marina; Biolo, Gianni; Simunic, Bostjan; Kokic, Tomislav; Pisot, Rado
Abstract: Problem: Gestational diabetes mellitus, defined as any carbohydrate intolerance first diagnosed during pregnancy, is associated with a variety of adverse outcomes, both for the mother and her child. Aim: To investigate the impact of a structured exercise programme which consisted of aerobic and resistance exercises on the parameters of glycaemic control and other health-related outcomes in pregnant women diagnosed with gestational diabetes mellitus. Methods: Thirty-eight pregnant women diagnosed with gestational diabetes mellitus were randomised to two groups. Experimental group was treated with standard antenatal care for gestational diabetes mellitus, and regular supervised exercise programme plus daily brisk walks of at least 30 min. Control group received only standard antenatal care for gestational diabetes mellitus. The exercise programme was started from the time of diagnosis of diabetes until birth. It was performed two times per week and sessions lasted 50–55 min. Findings: The experimental group had lower postprandial glucose levels at the end of pregnancy (P < 0.001). There was no significant difference between groups in the level of fasting glucose at the end of pregnancy. Also, there were no significant differences in the rate of complications during pregnancy and birth, need for pharmacological therapy, maternal body mass and body fat percentage gains during pregnancy, and neonatal Apgar scores, body mass and ponderal index. Neonatal body mass index was higher in the experimental group (P = 0.035). Conclusion: The structured exercise programme had a beneficial effect on postprandial glucose levels at the end of pregnancy.